PERILAKU KONSUMEN REMAJA DALAM MENGKONSUMSI MAKANAN CEPAT SAJI DI PIZZA HUT BASKO GRAND MALL PADANG - Maswati Maswati; Wirnelis Syarif; Wiwik Gusnita (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
This study is based on the behavior of juvenile consumers in consuming fast food at Pizza Hut Basko Grand Mall. This study aims to determine consumer behavior in consuming fast food. The type of research used is descriptive research. The population is teenage consumers who come to Pizza Hut Basko Grand Mall restaurant is not known the exact number and taken samples through incidental sampling. Primary data in this study obtained directly from the respondents with the format of questionnaire. Analysis technique by determining the frequency distribution of data and determine the level of achievement of respondents. The results showed that the behavior of juvenile consumers in consuming fast food at Pizza Hut Basko Grand Mall is good. The behavior of juvenile consumers in consuming fast food at Pizza Hut Basko Grand Mall with sub indicators of good knowledge. The behavior of juvenile consumers in consuming fast food at Pizza Hut Basko Grand Mall with sub indicators of good attitude.